2019
DOI: 10.1088/1755-1315/327/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Percentage Value of Membrane Integrity and Acrosome Integrity Spermatozoa in Simmental Liquid Semen with Addition Penicillin and Sweet Orange Essential Oil

Abstract: Growth of bacteria in the Simmental liquid semen is is the cause of the quality of liquid cement to be bad. The addition of antibiotics has been done to inhibit the growth of bacteria in the liquid semen. One of antibiotic that often used is penicillin. The addition of sweet orange essential oil is expected to further suppress the growth of bacteria because it contains antibacterial. The research objective was to determine the value of the percentage Membrane Integrity and Acrosome Integrity on Simmental liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The results of previous studies by adding a combination of penicillin and essential oils have been shown to increase the percentage of membrane integrity in Simmental spermatozoa [4]. In this research, the combination of gentamicin and the sweet orange essential oil is expected to further increase the percentage of whole spermatozoa membrane integrity in Simmental liquid semen.…”
Section: One Of the Success Factors Of Artificialmentioning
confidence: 66%
“…The results of previous studies by adding a combination of penicillin and essential oils have been shown to increase the percentage of membrane integrity in Simmental spermatozoa [4]. In this research, the combination of gentamicin and the sweet orange essential oil is expected to further increase the percentage of whole spermatozoa membrane integrity in Simmental liquid semen.…”
Section: One Of the Success Factors Of Artificialmentioning
confidence: 66%
“…Sweet orange essential oil containing limonene and linalool are toxic to bacteria [9]. The results of previous studies by adding a combination of penicillin and Sweet orange essential oil have been shown to increase the percentage of intact plasma membranes in Simmental spermatozoa [10]. In this research, a combination of gentamicin and sweet orange essential oil is expected to increase the percentage of spermatozoa acrosome integrity in Simmental bull liquid semen.…”
Section: One Of the Important Factors Of Artificialmentioning
confidence: 72%
“…From the data obtained, it has been shown that the addition of sweet orange essential oil increases the value of acrosome integrity spermatozoa Simmental bull percentage before semen equilibration. The higher level of administration of sweet orange essential oil will further increase the value of acrosome integrity spermatozoa [10]. Since it perhaps enhances membrane integrity and thus prevents cold shock.…”
Section: Resultsmentioning
confidence: 99%
“…(2018) with 40% found in Bali bull and 50% in Simmental bull during the observation of the hood acrosome intact. Sitepu and Marisa (2019) claimed that the acrosome plays an important role in the fertilization process for successful artificial insemination. The spermatozoa binding initiation to the zona pellucida will trigger the acrosome reaction which lead to the release and activation of acrosome enzymes, so that the spermatozoa are able to penetrate the zona pellucida.…”
Section: The Quality Of Frozen Semen Of Bali and Simmental Bullmentioning
confidence: 99%